Outcome of planned home births in an inner city practice. Issue 6816 (14th December 1991) - Ford, C; Iliffe, S; Franklin, O
Abstract : OBJECTIVE--To assess the outcome of pregnancy for women booking for home births in an inner London practice between 1977 and 1989. DESIGN--Retrospective review of practice obstetric records. SETTING--A general practice in London. SUBJECTS--285 women registered with the practice or referred by neighbouring general practitioners or local community midwives. MAIN OUTCOME MEASURES--Place of birth and number of cases transferred to specialist care before, during, and after labour. RESULTS--Of 285 women who booked for home births, eight left the practice area before the onset of labour, giving a study population of 277 women. Six had spontaneous abortions, 26 were transferred to specialist care during pregnancy, another 26 were transferred during labour, and four were transferred in the postpartum period. 215 women (77.6%, 95% confidence interval 72.7 to 82.5) had normal births at home without needing specialist help. Transfer to specialist care during pregnancy was not significantly related to parity, but nulliparous women were significantly more likely to require transfer during labour (p = 0.00002). Postnatal complications requiring specialist attention were uncommon among mothers delivered at home (four cases) and rare among their babies (three cases). CONCLUSIONS--Birth at home is practical and safe for a self selected population of multiparous women, but nulliparous women are more likely to require transfer to hospital during labour because of delay in labour. Close cooperation between the general practitioner and both community midwives and hospital obstetricians is important in minimising the risks of trial of labour at home.